2023
DOI: 10.1007/s00216-023-04943-w
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of exposure in urine of active smokers, non-smokers, and vapers

D. Gallart-Mateu,
P. Dualde,
C. Coscollà
et al.

Abstract: The exposure to smoking related products has been evaluated through urine illness risk marker determination through the analysis of urine samples of smokers and vapers. Biomarkers and their metabolites such as N-acetyl-S-(2-cyanoethyl)-L-cysteine (CEMA), N-acetyl-S-(3,4-dihydroxybutyl)-L-cysteine (DHBMA), N-acetyl-S-[1-(hydroxymethyl)-2-propen-1-yl)-L-cysteine (MHBMA), N-acetyl-S-(3-hydroxypropyl)-L-cysteine (3HPMA), 2R-N-acetyl-S-(4-hydroxybutan-2-yl)-L-cysteine (HMPMA), and N-acetyl-S-(3-carboxy-2-propyl)-L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In a previous study, 11 we evaluated exposure to tobacco and nicotine vaping through the urine control of six metabolites of acrylonitrile, acrolein and crotonaldehyde in urine samples of active traditional smokers, past strong smokers who moved to vaping, and non-smokers, which confirmed that N -acetyl- S -(2-cyanoethyl)- l -cysteine (CEMA) is present only in active smokers and that levels of 2 R-N -acetyl- S -(4-hydroxybutan-2-yl)- l -cysteine (HMPMA) and N -acetyl- S -[1-(hydroxymethyl)-2-propen-1-yl)]- l -cysteine (MHBMA) in vapers' urine are at the same level of magnitude as smokers and non-smokers. The level of N -acetyl- S -(3,4-dihydroxybutyl)- l -cysteine (DHBMA) in the urine of previous smokers reached similar values to those determined in non-smokers and it was also observed that levels of N -acetyl-hydroxy-propyl-cisteine (3HPMA) in urine showed a strong reduction on moving from smoking to vaping.…”
Section: Introductionmentioning
confidence: 86%
“…In a previous study, 11 we evaluated exposure to tobacco and nicotine vaping through the urine control of six metabolites of acrylonitrile, acrolein and crotonaldehyde in urine samples of active traditional smokers, past strong smokers who moved to vaping, and non-smokers, which confirmed that N -acetyl- S -(2-cyanoethyl)- l -cysteine (CEMA) is present only in active smokers and that levels of 2 R-N -acetyl- S -(4-hydroxybutan-2-yl)- l -cysteine (HMPMA) and N -acetyl- S -[1-(hydroxymethyl)-2-propen-1-yl)]- l -cysteine (MHBMA) in vapers' urine are at the same level of magnitude as smokers and non-smokers. The level of N -acetyl- S -(3,4-dihydroxybutyl)- l -cysteine (DHBMA) in the urine of previous smokers reached similar values to those determined in non-smokers and it was also observed that levels of N -acetyl-hydroxy-propyl-cisteine (3HPMA) in urine showed a strong reduction on moving from smoking to vaping.…”
Section: Introductionmentioning
confidence: 86%